Sinkretisme Islam dan Budaya Nusantara dalam Sedekah Laut Cilacap - Imam Mubarok; Satriyo Pambudi (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
The purpose of this study is to explore syncretism in the Sedekah Laut tradition at Teluk Penyu Beach, Cilacap, Central Java. This type of qualitative research uses library research or library research. The results of the research and discussion are the Cilacap Sea Alms tradition including syncretism. The conclusion of the study is that there is a syncretism between Nusantara culture and Islam in the series of events of the Cilacap Sea Alms tradition starting from night to day, so it requires an explanation that this is the beginning of Islamic teachings.